Assessing the effects of foreign direct investment and core macroeconomic indicators on tourism arrivals in Malaysia - Hashim, Asmawi; Razali, Ruzimas Ayu; Hashim, Emilda; Rambeli, Norimah; Ismail, Zuriadah (Journal of Islamic, Social, Economics and Development, 2025)
Tourism plays a vital role in Malaysia’s economic and social landscape, contributing significantly to government revenue, job creation, and community development. Defined as a social, cultural, and economic activity involving travel beyond one’s usual environment, tourism often stimulates broader economic growth. This study investigates how foreign direct investment (FDI), the exchange rate (ER), and gross domestic product (GDP) influence tourist arrivals in Malaysia between 1995 and 2024 using the Autoregressive Distributed Lag (ARDL) approach. The study seeks to accomplish three main objectives, which are to assess the strength of the relationship between tourism and the selected macroeconomic variables, to examine their short- and long-run effects, and to identify the factor that most dominantly influences tourist arrivals. The study employs the bounds test, error-correction model (ECM), Granger causality analysis, and the Cumulative Sum (CUSUM) stability test. The findings reveal the presence of a long-run relationship among all variables. However, only GDP exhibits a positive long-run effect on tourist arrivals, whereas FDI and the exchange rate show negative long-run relationships. In the short run, all variables also demonstrate significant effects on tourism. Moreover, the CUSUM test confirms model stability within the 5% confidence interval. These insights provide valuable guidance for policymakers in formulating strategies to strengthen Malaysia’s tourism sector and attract more international visitors.